HOMOSEKSUAL: ANALISIS HUKUM DAN NILAI MORAL DALAM ISLAM (STUDI MAWDLUI PERSPEKTIF TAFSIR IBNU KATSIR) - Joeha, Avif Alfiyah; Avif Alfiyah; Sugiarto, Fitrah; Nazila, Salwa Dama; Shofiyah, Shofiyah (MADINAH, 2025)
The phenomenon of homosexuality has become a complex issue in the context of global social and cultural developments, especially in the modern era which often encourages a shift in traditional values. In Islam, the story of the people of Luth in the Qur'an is often used as the main basis for evaluating this phenomenon, with an emphasis on the prohibition of homosexual behavior which is considered morally and spiritually deviant. This study aims to analyze the laws and moral values ​​related to homosexuality based on the perspective of Ibn Kathir's interpretation. As one of the classical tafsir books that has a wide influence in the Islamic scientific tradition, Ibn Kathir's Tafsir offers a rich and in-depth approach in interpreting the verses of the Qur'an related to homosexuality, especially the story of the people of Prophet Luth. This study uses the thematic method (maudu'i) by collecting and analyzing verses related to homosexuality in the Qur'an, as well as examining the interpretation given by Ibn Kathir. The results of the study show that Ibn Kathir firmly categorizes homosexuality as a deviant act according to sharia and morals, and emphasizes the negative social and psychological impacts of such behavior. In his interpretation, he also highlights the importance of preserving family values, and strongly warns against acts that are contrary to human nature. This study also reviews the relevance of the moral values ​​contained in the interpretation for the context of modern society, especially in facing the challenges and debates regarding the normalization of homosexuality. This study is expected to contribute to understanding the Islamic perspective on the issue of homosexuality, as well as strengthening moral and legal insights in order to build a society based on religious and humanitarian values.